E-025 Transorbital Carotid-Cavernous Fistula Embolization with Ruby Coils. (26th July 2014) - Milburn, J; Pansara, A; Perry, M; Vidal, G; Eubanks, B
Abstract : Purpose: A carotid cavernous fistula (CCF) is an abnormal arteriovenous connexion between the internal carotid artery (ICA) or the external carotid artery (ECA) and the cavernous sinus. Symptoms range from benign ocular disturbances and cranial nerve palsies to severe or rapid vision loss and intracranial haemorrhage. Primary treatment options include transvenous or transarterial embolization. Coil embolization of the cavernous sinus is often a long procedure using many small diameter microcoils with high radiation doses. The purpose of this case is to illustrate the use of larger diameter (0.020 inch) Ruby coils (Penumbra Inc.) as a highly efficient alternative method of embolization. Methods: An 84-year-old woman presented to her local emergency room for progressive diplopia and loss of visual acuity over several weeks. Computed tomography (CT) of the head and CT angiography (CTA) revealed enlarged superior ophthalmic veins suggesting a CCF. Cerebral angiography was performed demonstrating an indirect CCF supplied by small branches of both the right and left internal and external carotid arteries with primary venous drainage into the right superior ophthalmic vein. Transvenous treatment from the femoral approach at the same setting was unsuccessful due to complete occlusion of the inferior petrosal sinus (IPS) bilaterally. Definitive treatment was then performed via direct transorbital approach. An oculoplastic surgeon provided direct surgical exposure to the right superior ophthalmic vein. The neurointerventionalist then punctured the exposed vein with a micropuncture needle to advance a 4-French short sheath. A Penumbra PX SLIM microcatheter was then advanced to the posterior cavernous sinus at the midline. 7 Ruby coils were deployed into the cavernous sinus and right SOV to occlude the CCF. Occlusion of the CCF was achieved by deployment of 150 cm of Penumbra 0.020-inch calibre detachable coils. Procedure time was 21 min from introduction of the 1 st coil to microcatheter removal. Results: Complete occlusion of the CCF was demonstrated on the final right and left common carotid angiograms. Her visual acuity improved on postoperative day 1. At her 1 week clinic visit, visual acuity was nearly at baseline, proptosis was improved, and diplopia improved. Her 6 th nerve palsy was 50% improved on the 3 month follow-up. Conclusion: Embolization of an indirect CCF may be performed efficiently using large diameter Ruby coils. This case presentation illustrates a direct transorbital approach via the SOV with operative photographs and pertinent angiographic images. The coil time was short due to the efficiency of the large (0.020 inch) diameter and long available lengths of Ruby coils. Disclosures: J. Milburn: 3; C; Penumbra, Inc.. A. Pansara: None. M. Perry: None. G. Vidal: 3; C; Penumbra, Inc., Covidien. B. Eubanks: None.